Environmental education for the efficient use of drinking water in fifth graders from tree educational institutions in the city of Tacna - Cori Tenorio, María Briguitte (2020)
The research aimed to develop an environmental educational program to raise awareness among the students of the three educational institutions, on the efficient use of drinking water, through information workshops, recreational activities for students, teachers and parents, 265 fifth graders from educational institutions were worked; Colonel Bolognesi, Argentina and Santa Cruz, before implementing the program applied a pre-test of 30 questions in order to know the performance in the efficient use, recycling, optimization of water. Subsequently a post test was applied for, the data was tested using the statistical sign test. Results indicate that low levels of efficient use were reduced from 36.6% to 1.0%, moderate levels fell from 59.6% to 34.0%, while high efficiency levels increased from 3.8% to 65.0%. With regard to water recycling, values expressing low levels of efficiency were reduced from 32.1% to 0.0%, average levels from 58.9% to 24.2% and high levels of water use efficiency increased significantly from 9.1% to 75.8%, while in water optimization, found results show that low levels were reduced from 30.6% to 1.1%, moderate levels of 66.4% to 35.5%, favourably high levels of water use efficiency increased from 3.0% to 63.0%, all comparisons were 95% confidence. Finally, the Argentine Republic educational institution excelled in all aspects evaluated at the highest levels, which implies that the environmental awareness of its students is adequate